Business Networking: Transformasi Meuju Perusahaan Kelas Dunia - Lena Ellitan . (Jurnal Manajemen Maranatha, 2009)
World class manufacturers which operate in the global market must have a world class performance. In this circumstance, having the right product in the right place, and in the right time will encourage manufacturers to win the global competition, on the other hand they do not have the resources and competencies. In this case, collaboration amongst business partners is needed to support the process of product innovation and to achieve efficiency and efectiveness in their business activities. As a result, customer value creation in business networking becomes an important issue in developing collaboration to improve manufacturing competitiveness. This paper discusses how manufacturers achieve their sustainable competitive advantage through value creation in business networking. Based on the literature review, to become a world class manufacturer, three core strategies are needed; focus on consumer, focus on quality, and focus on many supporting competencies such as employee empowerment, product development through research and development, corporate culture amongst business partners, and radical thinking.Keywords: Business Transformation, Collaboration, Business Networking, World Class Manufacturer